Composite material automobile top cover middle cross beam and forming method thereof
By using a combination of continuous glass fiber reinforced polypropylene material and metal mesh, combined with electroplating phosphating and molding processes, the problems of high carbon fiber price and low glass fiber strength are solved, and the crossbeam in the car roof is lightweight and high strength is achieved. , reduces production costs and is suitable for large-scale production.
Patent Information
- Application Number
- CN202411418022.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-11
- Publication Date
- 2025-01-10
AI Technical Summary
In the prior art, carbon fiber thermosetting resin composite solutions are expensive and difficult to recycle. Glass fiber nylon composite solutions increase structural size due to low material strength, and metal-composite molding process has unstable connection performance and relatively strong finished product. Poor problem.
Continuous glass fiber is used as the reinforcement of composite material, polypropylene is the matrix, and a metal mesh is added to enhance the strength of the material. It is designed as a W-shaped cross-sectional structure. The metal mesh is electroplating and phosphating, combined with a double steel belt press and molding. Process to improve the connection performance between metal and composite materials.
It realizes that the beam is lighter under the premise of meeting the strength and stiffness requirements, reduces material costs, improves the strength and production efficiency of the finished product, meets environmental protection requirements, and is suitable for large-scale production.
Smart Images

Figure CN119283976A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of automobile lightweight design, and in particular to a composite material automobile roof middle cross beam and a molding method thereof. Background Art
[0002] In recent years, the share of new energy vehicles in the domestic and international automobile markets has continued to increase, and the automobile industry has also shifted from traditional automobile production to new energy vehicle production. The requirements for lightweighting are more stringent for new energy vehicles. Among them, the crossbeam in the top cover of the car is one of the important load-bearing parts of the car body. The traditional crossbeam is made of metal and is heavy, which is difficult to meet the lightweight requirements of new energy vehicles.
[0003] Existing lightweight solutions mostly use composite materials to achieve the purpose of lightweight, but there are still some problems. CN111038596A discloses a carbon fiber composite car roof middle beam, with carbon fiber as a reinforcement, epoxy resin as a matrix, and the cross beam cross section adopts an M-shaped structure design. Compared with traditional metal cross beams, it is light in weight and high in specific strength. However, the price of carbon fiber is relatively high, and thermosetting resin is used at the same time, which faces recycling problems in the later stage. With the increasing environmental protection requirements today, this solution is difficult to mass produce and use. CN113147905B discloses a continuous glass fiber reinforced nylon composite roof cross beam, which is used as a reinforcement of nylon composite material, and has lower cost and is easy to recycle compared to carbon fiber as a reinforcement. However, due to the use of lower strength glass fiber as a reinforcement, a cavity is set between the upper and lower plates of the cross beam to increase the strength, resulting in an increase in the longitudinal size of the cross beam, an increase in the occupied space, and the upper and lower plates need to be connected twice, which increases the process complexity and molding time, and the production efficiency is low. Metal-composite composite materials are made by stacking metal mesh and composite prepreg layers and bonding them together with a resin matrix. Using metal to reinforce composite materials is a common method to achieve lightweight and improve the strength of composite materials, but the existing metal-composite molding process has problems such as unstable connection performance between metal mesh and composite materials and poor strength of finished products. Summary of the invention
[0004] The existing carbon fiber thermosetting resin composite material solution is expensive and difficult to recycle; the glass fiber nylon composite material solution has a relatively low material strength, which results in an increase in the structural size. In view of these problems, the present invention provides a composite material automobile roof middle crossbeam and a molding method thereof, which can achieve lightweighting of the crossbeam while meeting the strength and stiffness requirements. At the same time, the provided molding method can improve the connection performance between metal and composite materials, thereby improving the strength of the finished product.
[0005] The present invention provides the following technical solutions:
[0006] First, a composite material automobile roof middle cross beam is provided. The middle cross beam is a material composed of metal and composite materials, continuous glass fiber is used as the reinforcement of the composite material, polypropylene is used as the matrix, and a metal layer is added to enhance the strength of the material, and the metal layer is a metal mesh. The overall ply design of the middle cross beam material is a structure in which a layer of metal mesh is sandwiched between two layers of composite materials. The cross-sectional shape of the middle cross beam is designed to be W-shaped and a flange is set at the end. The overall design along the length direction is an arc that is slightly convex upwards. The left and right end faces are connected to the side beams of the automobile, and the end faces are provided with bolt holes and buckle holes.
[0007] Secondly, the present invention also provides a corresponding method for forming a cross beam in a top cover of an automobile, comprising the following steps:
[0008] (1) Cut the metal mesh into corresponding shapes and sizes and perform surface electroplating and phosphating treatment;
[0009] (2) preparing a glass fiber polypropylene prepreg unidirectional tape and cutting it into corresponding shapes and sizes;
[0010] (3) Preparing a metal-composite laminate: Laying the prepreg and the metal mesh according to the design requirements, and rolling them using a double steel belt press to obtain a semi-finished metal-composite laminate;
[0011] (4) The metal-composite laminate is processed by a compression molding method to form a middle cross beam structure shape to obtain a final product.
[0012] Preferably, the composite material layer of the cross beam in the automobile roof is a continuous glass fiber reinforced polypropylene composite material, and the metal mesh layer is 304 stainless steel. The material paving is designed to be three layers, which are composite material, metal mesh, and composite material from bottom to top. The thickness of the two layers of composite material is 0.8mm, the thickness of the single layer of prepreg is 0.2mm, the thickness of the metal mesh layer is 0.4mm, and the total thickness of the material is 2mm. With the length direction of the cross beam as the 90° direction, the lower layer of prepreg is laid in the order of 90°, 0°, 90°, and 0°, and the upper layer is laid in the order of 0°, 90°, 0°, and 90°.
[0013] The specific steps of the composite material automobile roof middle crossbeam forming method are as follows:
[0014] (1) First, cut the metal mesh into the shape and size corresponding to the design, then use an acidic metal surface cleaner to treat the metal mesh to remove surface oil and impurities, and then use an activation liquid to activate the surface. Finally, perform electroplating and phosphating, and then clean and dry it for use.
[0015] (2) In the preparation of the composite material prepreg, the resin matrix is polypropylene mixed with a certain amount of compatibilizer and coupling agent. Excluding the coupling agent, polypropylene accounts for 35% of the total mass fraction of the prepreg, the compatibilizer accounts for 5%, and the continuous glass fiber accounts for 65%. The polypropylene, compatibilizer and coupling agent prepared according to the requirements are uniformly mixed in a high-speed mixer, and then the mixed molten resin is squeezed into the impregnation mold through a screw extruder, and continuous glass fiber is introduced at the same time, so that the glass fiber and the resin are impregnated in the die head, and then the impregnated continuous glass fiber impregnated material is drawn out through a traction device, and finally rolled and cooled to obtain a continuous glass fiber reinforced polypropylene unidirectional prepreg tape.
[0016] (3) The cut prepreg unidirectional tapes and metal mesh are layered as required, and the laminated composite material laminate is placed in a double steel belt press for continuous compression molding. The laminated composite material is first infrared heated in the press, and then rolled by upper and lower symmetrical rollers to bond the multiple layers of material together, and finally cooled to obtain the composite material laminate.
[0017] (4) The composite laminate prepared by the above process is used as the raw material and is formed by molding. First, the laminate is heated by infrared heating. At the set temperature and time, the laminate reaches a softened molten state, and the heating is stopped and kept warm. Prior to this, a release agent is applied to the upper and lower mold surfaces of the mold, and preheating is started. After the mold is preheated, the molten composite laminate is sent to the mold station, the mold is closed, and the temperature and pressure are increased, the temperature is kept and the pressure is maintained, and the temperature and pressure are reduced. After that, the mold is opened and the top cover middle beam blank is taken out. Finally, the blank is processed by trimming and opening holes to obtain the final top cover middle beam part.
[0018] Compared with the prior art, the present invention has the following beneficial effects:
[0019] 1. The present invention adopts metal mesh and glass fiber reinforced polypropylene composite materials, which combines the advantages of metal materials and composite materials and improves the performance of the middle cross beam of the automobile roof. The cross section adopts a W-shaped structure, which enhances the strength and rigidity of the middle cross beam and reduces the space occupied. Compared with the existing carbon fiber reinforced epoxy resin composite materials, the present invention adopts metal mesh and continuous glass fiber reinforced thermoplastic resin composite materials. The material price is low and easy to recycle. It meets environmental protection requirements and can be mass-produced and used. Compared with glass fiber reinforced nylon composite materials, it has higher strength, smaller space occupation and higher production efficiency.
[0020] 2. In the corresponding forming method, the surface of the metal mesh is electroplated and phosphated. Compared with other treatment methods, the roughness increases after phosphating process, and the concave-convex structure distribution on the surface of the metal mesh is more uniform and delicate. Through adhesion test analysis, it is found that the adhesion of the stainless steel surface after phosphating is enhanced, which increases the mechanical connection characteristics with other materials, improves the adhesion between the metal mesh and the resin matrix, and enhances the overall strength of the material.
[0021] 3. The semi-finished composite laminates are prepared by double steel belt presses, which improves the interface bonding effect between different materials. Finally, the compression molding process is carried out, that is, the layers of materials are coupled twice, which further improves the connection strength between the material interfaces. The production process is also more flexible and controllable. The semi-finished laminates can be stored for a long time and can also be manufactured into parts of other shapes and sizes as needed. Preparing sufficient laminates in advance can improve the continuity of the compression molding process and thus improve production efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 It is a schematic diagram of the structure of the cross beam material layer in the top cover;
[0023] Figure 2 This is the axonometric view of the crossbeam in the composite material car roof;
[0024] Figure 3 This is the main view of the middle beam;
[0025] Figure 4 It is a partial view of the end of the middle beam;
[0026] Figure 5 It is the cross-section of the middle beam;
[0027] Figure 6 It is a schematic diagram of the process of preparing composite laminates by double steel belt press molding;
[0028] Figure 7 It is a schematic diagram of the process of compression molding of the middle cross beam;
[0029] In the figure:
[0030] 1. Composite material layer; 2. Metal mesh layer; 3. Middle cross beam body; 4. Bolt hole; 5. Clip hole. DETAILED DESCRIPTION
[0031] The following is a further detailed description of the embodiments of the present invention in conjunction with the accompanying drawings and examples. The following examples are used to illustrate the present invention but are not intended to limit the scope of the present invention.
[0032] In order to solve the drawbacks of the existing solutions, the present invention uses a composite material plus metal mesh to replace the existing materials and designs a reasonable structure and molding process. On the premise of meeting the requirements of lightweight and strength and stiffness, it solves the problem of the high price of carbon fiber and the low strength of glass fiber. It also designs a reasonable structure to reduce the space occupied, and at the same time provides a corresponding molding process to improve the connection performance between metal and composite materials and improve production efficiency.
[0033] The material selection of the present invention takes various factors into consideration. Compared with traditional thermosetting composite materials, the advantages of thermoplastic composite materials are as follows: thermoplastic composite materials take less time to form; they can be processed by secondary thermoplastic forming; the storage method is more convenient, and it can be stored at room temperature and pressure; it is green and environmentally friendly and can be recycled. Polypropylene has the characteristics of excellent mechanical properties, low price, and light weight. 304 stainless steel metal mesh has good mechanical properties, corrosion resistance, high temperature resistance, and low cost. The forming method provided by the present invention utilizes electroplating phosphating process, double steel belt lamination process, and compression molding process to enhance the interface bonding force between various materials, improve the mechanical properties of the finished product, and has the advantage of easy realization of automated production.
[0034] In summary, the materials selected are continuous glass fiber reinforced polypropylene composite materials and 304 stainless steel wire mesh with a specification of 30 mesh. Figure 1 As shown, the material covering design is three layers, from bottom to top, composite material layer 1, metal mesh layer 2, composite material layer 1. The thickness of the two composite material layers is 0.8mm, the thickness of the single prepreg layer is 0.2mm, the thickness of the metal mesh layer is 0.4mm, and the total thickness of the material is 2mm. Since the middle crossbeam is mainly subjected to downward pressure, the pressure is dispersed to the side beams on both sides through the crossbeam, so the crossbeam is required to have strong compressive and tensile properties. With the length direction of the crossbeam as 90°, the lower layer of prepreg unidirectional tape is laid in the order of 90°, 0°, 90°, and the upper layer is laid in the order of 0°, 90°, 0°, 90°. This laying method can better improve the compressive performance of the crossbeam, disperse the load to the side beams, and enhance the stability of the crossbeam and the top cover.
[0035] like Figure 2 and Figure 5 As shown in the figure, the cross-section of the beam is designed to be W-shaped and a flange is set at the end, which not only enhances the strength and rigidity of the beam but also reduces the longitudinal dimension and the space occupied. The vertical support structure of the beam is set to have a certain slope, which can improve the stability of the support and facilitate demolding after molding. The corners of the beam structure are set with arcs to reduce stress concentration. Figure 3 As shown, the crossbeam is designed to be slightly convex upward along the length direction, so that it is more in line with the force characteristics to improve the strength and rigidity of the crossbeam. Figure 2 and Figure 4 As shown, the left and right end faces are connected to the side beams of the automobile, and bolt holes 4 and buckle holes 5 are arranged on the end faces for mounting the cross beam to the side beams, and are also used for positioning and fixing during compression molding.
[0036] Taking into account the anti-corrosion and anti-electrical performance of the center beam after molding, and in order to avoid fatigue and corrosion that may weaken the bonding performance between the metal layer and the composite layer, it is considered to completely wrap the metal layer in the composite material layer. Therefore, when cutting the raw materials, the metal mesh layer is cut 2mm inward on all sides. After compression molding, the metal mesh layer can be completely wrapped in the composite material layer, avoiding the above-mentioned problems.
[0037] Secondly, the present invention also provides a corresponding composite material automobile roof middle crossbeam forming method, comprising the following steps:
[0038] (1) Cut the metal mesh into corresponding shapes and sizes and perform surface phosphating treatment;
[0039] (2) preparing a glass fiber polypropylene prepreg unidirectional tape and cutting it into corresponding shapes and sizes;
[0040] (3) Preparing a metal-composite laminate: Laying the prepreg and the metal mesh according to the design requirements, and rolling them using a double steel belt press to obtain a semi-finished metal-composite laminate;
[0041] (4) The composite metal laminate is processed by a compression molding method to form a middle cross beam structure shape to obtain a final product.
[0042] Specifically, in step (1), the metal mesh is first cut into the shape and size corresponding to the design, and then the metal mesh is surface treated by electroplating phosphating process. Metal electroplating phosphating process is a commonly used metal surface pretreatment method. The principle is to put the metal treated with acidic or alkaline solution into the phosphating solution, and perform electrochemical reaction under the stimulation of electric current, so that the surface of the metal forms a layer of phosphate film with uniform thickness and density in the phosphate solution containing manganese, iron and zinc. The phosphate film is coated on the metal surface, which can improve the connection characteristics of the metal surface.
[0043] The specific steps of electroplating phosphating process are as follows:
[0044] S1. Remove impurities such as oil on the surface of the metal mesh, which is conducive to the subsequent phosphating treatment: soak the cut stainless steel metal mesh in an acidic cleaning agent and ultrasonically clean it for 10 minutes. After completion, remove it and clean it, and then dry it in a blast drying oven at a temperature of 60°C for 5 minutes;
[0045] S2. Since there is a layer of passivation film on the surface of the metal mesh, the phosphating process has a poor effect. Therefore, it is necessary to remove the oxide film and activate the metal mesh: put the cleaned and dried metal mesh into a mixed solution of nitric acid and hydrochloric acid with a volume fraction of 10% and 3%, respectively, and activate it at room temperature for 1 minute to improve the effect of the phosphating process;
[0046] S3. Prepare electroplating phosphating solution: the specific composition of the phosphating solution is: ZnO 4.0g / L, CaCl2 4.0g / L, H3PO3 5% (volume fraction), tartaric acid 4g / L, sodium chlorate 3g / L, and the pH value of the phosphating solution is adjusted to pH 3 by using 3 mol / L NaOH solution;
[0047] S4. Electroplating phosphating treatment: put the activated metal mesh into the electroplating phosphating solution, use water bath heating to keep the phosphating solution temperature at 80°C, and the current density of electrochemical phosphating is 20mA / cm 2 , lasting 20 minutes;
[0048] S5. After the reaction is completed, the metal mesh is washed with clean water and dried in a blast drying oven at 60°C for 5 minutes. The electroplating phosphating treatment of the metal mesh is completed.
[0049] Under SEM, it was observed that a layer of phosphate film appeared on the surface of the stainless steel metal mesh after electroplating phosphating treatment. There were obvious zinc calcium phosphate crystals on the surface of the phosphate film, showing a peak-shaped convex structure and uniform distribution. It can be seen that after the metal mesh was treated by electroplating phosphating process, the surface glossiness decreased, the roughness increased, and the peaks and concave-convex structures on the surface were more evenly and delicately distributed.
[0050] The electroplating phosphating process has the following advantages: first, the phosphating process is widely used in metal surface treatment, and the process is simple, the reaction time is short, and it is economical and practical. Secondly, the phosphating film formed on the metal surface has more micro-mechanical interlocking structures, which can improve the interface bonding performance between metal and resin. Finally, the phosphating film also has electrical insulation and corrosion resistance, which can reduce the corrosion of the material.
[0051] Furthermore, the bonding performance between the stainless steel mesh and the resin-based composite material after electroplating and phosphating was tested.
[0052] Two groups of comparative experiments were set up, one group was a metal mesh without treatment, and the other group was a metal mesh after sandblasting, polishing, pickling and corrosion. Since the metal mesh has a porous mesh structure, its adhesion cannot be directly measured. The metal mesh was replaced with the same metal block, and the same treatment was performed on it before testing. After testing with an adhesion tester, it was found that the adhesion value of the untreated sample was 10MPa, the maximum adhesion of the pickling and corrosion sample was 18.4MPa, and the maximum adhesion of the electroplating phosphating sample was 31MPa. It is proved that electroplating phosphating treatment can effectively enhance the adhesion between the metal mesh and the resin, thereby enhancing the mechanical properties of the material.
[0053] Specifically, the matrix resin of the composite material prepreg in step (2) is polypropylene mixed with a certain amount of compatibilizer and coupling agent. Excluding the coupling agent, polypropylene accounts for 35% of the total mass fraction of the prepreg, the compatibilizer accounts for 5%, and the continuous glass fiber accounts for 65%. The continuous glass fiber reinforced polypropylene unidirectional prepreg tape is prepared by melt impregnation. The compatibilizer is maleic anhydride grafted polypropylene, and the coupling agent is a silane coupling agent. Polypropylene, compatibilizer and coupling agent are mixed in a ratio of 100 ml of coupling agent per 100 kg of polypropylene and compatibilizer to enhance the bonding force between glass fiber and resin.
[0054] The use of compatibilizers and coupling agents has the following advantages: Maleic anhydride grafted polypropylene contains active reaction groups, which can undergo esterification reaction with the surface of glass fiber, play a good bonding role on the fiber, and at the same time, it has good compatibility with polypropylene and can improve the mechanical properties of the product. The structure of silane coupling agent is a bifunctional organic silicon compound X3SiY, with a hydrolyzable group at the X end and a non-hydrolyzable organic functional group at the Y end. When using silane coupling agent, the coupling agent and glass fiber undergo dehydration condensation reaction on its surface to form a chemical bond, which enhances the bonding performance of the resin and glass fiber from a microscopic perspective, improves the interfacial adhesion between the resin and glass fiber, and thus improves the overall mechanical properties of the composite material.
[0055] The preparation method of the prepreg comprises the following steps:
[0056] S1. Put polypropylene, compatibilizer and coupling agent into a high-speed mixer according to the above proportions and mix them evenly to obtain a resin matrix mixture;
[0057] S2, adding the matrix mixture obtained in the above step S1 into a twin-screw extruder, heating it in the extruder to form a high-temperature melt, and then extruding the melt into a dipping mold. The heating temperature of the extruder is 160°C to 220°C, and the heating temperature of the dipping mold is 220°C;
[0058] S3, the continuous glass fiber is drawn out from the creel, and the fiber is spread and evenly distributed through the guide roller group, and then the fiber is preheated by an infrared heating device at a preheating temperature of 180°C, and then enters the impregnation area for impregnation. Then a certain pressure is applied by the pressure roller to control the resin content, and finally the prepreg unidirectional tape is cooled and rolled up.
[0059] Among them, polypropylene, compatibilizer and coupling agent are evenly mixed as the impregnation material, which saves the process of surface treatment of glass fiber and improves production efficiency. The heating temperature of the impregnation mold is 180℃~220℃, preferably 220℃. When the impregnation temperature is too low, the impregnation effect of glass fiber and matrix is poor, and the bubbles and pores generated increase, which affects the quality of prepreg and the interface bonding performance between fiber and matrix; when the impregnation temperature is too high, the compatibilizer and coupling agent are prone to degradation, reducing the interface bonding performance.
[0060] The preparation of prepregs by melt impregnation has the following advantages: the matrix resin is made into a molten state, so the prepreg volatilizes very little, reducing the probability of pores inside the fiber and no chemical pollution. Secondly, by controlling parameters such as temperature, pressure and impregnation speed, it can ensure that the resin is evenly coated on the glass fiber, thereby obtaining a prepreg with stable quality. Finally, the prepreg prepared by melt impregnation usually has good performance. The resin can fully infiltrate the glass fiber to form a good bond, thereby improving the mechanical properties, thermal properties and durability of the composite material.
[0061] Specifically, in step (3), the composite laminate is paved with two layers of composite materials, one layer of metal mesh in the middle. After the metal mesh and prepreg unidirectional tape are cut into corresponding shapes and sizes, the lower layer of prepreg unidirectional tape is laid in the order of 90°, 0°, 90°, 0°, and the upper layer is laid in the order of 0°, 90°, 0°, 90°, and then the metal mesh that has been electroplated and phosphating is laid between the two layers of composite materials. Figure 6 As shown, the laminated composite material is placed in a double steel belt press for continuous roll forming to obtain a composite laminate.
[0062] The preparation method of the composite laminate is specifically as follows:
[0063] S1. Lay the cut prepreg and metal mesh according to the above requirements, put them into the inlet of the double steel belt press, and the steel belt rolls to transfer the laminated composite material to the next process;
[0064] S2, first pass through the infrared heating area, the temperature is 160 ℃ ~ 220 ℃, so that the matrix resin in the prepreg becomes molten state, which is convenient for combining with the metal mesh;
[0065] S3, then enter the rolling part, the rollers outside the upper and lower steel belts apply pressure inward, rolling the laminated composite material to tightly combine the molten resin and the metal mesh;
[0066] S4. Since the present invention is a thermoplastic composite material, it finally enters the cooling area to cool the rolled composite laminate to room temperature, and the laminate preparation is completed.
[0067] Among them, the entrance angle of the double steel belt press can be adjusted to adapt to laminates of different thicknesses. By controlling the pressure between the upper and lower steel belts, the thickness of the laminate can be adjusted. At the same time, giving the laminate a certain pressure is conducive to making the composite material and the metal mesh tightly bonded together. Considering that the laminate needs to be molded in the subsequent steps, the thickness of the finished product after molding is 2mm. In order to reduce the fatigue of the fiber and the metal mesh and prevent fracture during molding to affect the final quality of the finished product, the spacing between the upper and lower layers of steel belts is controlled to 2.1mm, leaving a certain working stroke for the molding process, and allowing the fibers and metal mesh in the laminate to have a certain stretching margin. The speed range of the steel belt is 0.3m / s to 0.5m / s, preferably 0.4m / s. The appropriate molding speed can improve production efficiency, and there is also sufficient time for the resin to impregnate the metal mesh, which is conducive to discharging the gaps in the laminate and improving the interface bonding between the metal and the composite.
[0068] The use of a double steel belt press to prepare composite laminates has the following advantages: First, by using a double steel belt press to prepare laminates, the metal and composite materials can be tightly combined, and the distribution and compaction of the resin matrix are more uniform, which effectively enhances the overall strength and stiffness of the laminate. This combination can avoid interlaminar shear to a certain extent and improve the bearing capacity of the sheet. Secondly, the molding process of the double steel belt press is relatively stable, and the parameters can be controlled more accurately to ensure the stability of product quality. Finally, the preparation of laminates by a double steel belt press can easily realize an automated production line, improve production efficiency, reduce manual operations, and reduce production costs.
[0069] Preferably, in the last step of the above-mentioned laminate preparation process, the laminate is cooled to room temperature, which improves the integrity of the laminate preparation process, facilitates transportation and storage, and can be cut into other shapes and sizes to prepare more different parts in the later stage. However, considering the actual production process, compression molding will be carried out next, and the composite laminate needs to be heated to a softened molten state. Therefore, in actual production, the cooling step can be omitted, and the high-temperature laminate can be directly transferred to the compression molding process for compression molding, which not only reduces energy consumption, but also reduces process time and improves production efficiency.
[0070] Preferably, it is considered that after compression molding, the blank needs to be post-processed such as trimming and opening holes in order to obtain the middle cross beam part of the top cover. However, this will expose the metal mesh layer in the middle of the composite material layer, reducing the corrosion resistance and electrical insulation of the part. In the later stage, it may cause a decrease in the interfacial bonding force between the metal mesh layer and the composite material layer, resulting in material stratification and reduced mechanical properties of the part. Therefore, in the laminate preparation step, the holes on the left and right ends of the middle cross beam corresponding to the metal mesh and prepreg are cut out in advance, and the bolt holes and buckle holes in the metal mesh are cut 1mm more toward the outer circle. Then lamination is performed according to the above steps, so that the metal mesh is coated in the composite layer, avoiding the above risks.
[0071] Specifically, Figure 7 The figure shows a schematic diagram of the compression molding process. Step (4) uses the composite laminate prepared in step (3) as a raw material and adopts a compression molding method to perform molding. First, the composite laminate is heated until the laminate reaches a softened molten state, and the heating is stopped. A release agent is applied to the upper and lower mold surfaces of the mold, and preheating is started. After the mold is preheated, the molten composite laminate is sent to the mold station, the mold is closed, and the temperature and pressure are increased, the temperature and pressure are maintained, and the temperature and pressure are reduced. After that, the mold is opened and the top cover middle beam blank is taken out. Finally, the blank is subjected to post-processing such as trimming and hole opening to obtain the final top cover middle beam part.
[0072] The specific steps of molding the cross beam in the top cover are as follows:
[0073] S1, placing the composite laminate in step (3) into an infrared heating device for preheating at a temperature of 180° C., so that the resin matrix reaches a molten softening state;
[0074] S2. Apply release agent evenly on the upper and lower mold surfaces of the molding mold to facilitate subsequent demolding of the workpiece. Start mold preheating, and the mold preheating temperature is 170℃;
[0075] S3. After the preheating of the laminate and the mold is completed, the laminate is placed in the mold station. Figure 4 As shown, in step (3), holes have been opened at the left and right end surfaces of the laminate, and the laminate is fixed to the lower mold using positioning pins using a total of four bolt holes 4 on the left and right;
[0076] S4, the upper die is pressed down quickly, and after it contacts the laminate, it is slowly advanced, and the temperature and pressure are continuously raised. After reaching the predetermined temperature and pressure, it is maintained for a certain time. After reaching the set time, the temperature and pressure are lowered, the die is opened, and the middle cross beam blank is taken out;
[0077] S5. Since holes have been opened at corresponding positions of the laminate in step (3), the blank is finally processed by trimming, deburring, etc. to obtain the crossbeam part of the top cover.
[0078] The mold is heated from a preheating temperature of 170°C to 200°C, and when the mold pressure reaches 10MPa, the pressurization is stopped and maintained for 10 minutes. The polypropylene is allowed to reach a molten state again under high temperature and high pressure, and is fully fused and impregnated with the metal mesh and glass fiber.
[0079] The advantages of using compression molding to prepare the crossbeam are as follows: First, in step (3), a double steel belt press is used to prepare the laminate so that the resin is impregnated into the glass fiber and the metal mesh. In step (4), compression molding is used to produce a secondary impregnation under high temperature and high pressure, which makes the interlayer bonding effect of the material better and improves the product quality. Secondly, the compression molding product has high dimensional accuracy and is easy to ensure quality, and can be applied to the production of complex surface products. Finally, compression molding is easy to realize automated production, improve production efficiency, reduce manual operations, and reduce production costs.
[0080] The composite material automobile roof middle cross beam and its forming method of this embodiment solve the problem that the use of carbon fiber is expensive and difficult to recycle, and the use of glass fiber has low strength and occupies a large space in terms of materials and structure. At the same time, the electroplating phosphating metal mesh is used in the forming process to enhance the interface bonding force between the metal and the resin. The laminate is prepared by a double steel belt press, and the middle cross beam product is prepared by compression molding, so that the resin, glass fiber and metal mesh are coupled and bonded twice, which enhances the mechanical properties of the finished product. The designed forming method is easy to realize automated production, which can improve production efficiency and reduce production costs.
[0081] The embodiments of the present invention are provided for the purpose of illustration and description. Although the embodiments of the present invention have been shown and described above, it can be understood that the above embodiments are exemplary and cannot be understood as limitations of the present invention. Ordinary technicians in this field can change, modify, replace and deform the above embodiments within the scope of the present invention.
[0082] Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments, or to make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A composite material automobile roof middle cross beam and a forming method thereof, characterized in that: The invention comprises a beam body and a corresponding forming method.
2. The composite material automobile roof middle cross beam and the molding method thereof according to claim 1, characterized in that: The main body of the crossbeam adopts a structure in which two layers of composite materials are sandwiched by a layer of metal mesh; continuous glass fiber is used as the reinforcement of the composite material, polypropylene is used as the matrix, and the metal layer is 304 stainless steel metal mesh; the cross-sectional shape of the crossbeam is designed to be W-shaped and a flange is provided at the end; the overall design along the length direction is a slightly convex arc, and the left and right end faces are connected to the side beams of the car. Bolt holes and snap holes are provided on the end faces for installing the crossbeam on the side beam, and are also used for positioning and fixing during compression molding; arcs are provided at the corners of the crossbeam structure.
3. The composite material automobile roof middle cross beam and the forming method thereof as claimed in claim 2, characterized in that: The material cladding is designed to be three-layer, with two composite material layers each having a thickness of 0.8 mm, a single prepreg layer having a thickness of 0.2 mm, a metal mesh layer having a thickness of 0.4 mm, and a total material thickness of 2 mm. With the length direction of the beam being 90°, the lower prepreg layer is laid in the order of 90°, 0°, 90°, 0°, and the upper layer is laid in the order of 0°, 90°, 0°, 90°.
4. The composite material automobile roof middle cross beam and the molding method thereof according to claim 1, characterized in that: The corresponding forming method comprises the following steps: S1. Cut the metal mesh into corresponding shapes and sizes and perform surface electroplating and phosphating treatment; S2, preparing a glass fiber polypropylene prepreg unidirectional tape by a melt impregnation method, and cutting it into corresponding shapes and sizes; S3, preparing a metal-composite laminate: draping the prepreg and the metal mesh according to the design requirements, and rolling them using a double steel belt press to obtain a semi-finished metal-composite laminate; S4. The metal composite laminate is processed by a compression molding method to form a middle cross beam structure shape to obtain a final product.
5. The composite material automobile roof middle cross beam and the forming method thereof as claimed in claim 4, characterized in that: The electroplating phosphating process described in step S1 includes: cutting the metal mesh into the shape and size corresponding to the design, then treating the metal mesh with an acidic metal surface cleaner to remove surface oil and impurities, then activating the surface with an activation solution, and finally electroplating phosphating, and then cleaning and drying for standby use.
6. The composite material automobile roof middle cross beam and the molding method thereof as claimed in claim 4, characterized in that: The resin used in step S2 is polypropylene mixed with a certain amount of compatibilizer and coupling agent; excluding the coupling agent, polypropylene accounts for 35% of the total mass fraction of the prepreg, the compatibilizer accounts for 5%, and the continuous glass fiber accounts for 65%.
7. The composite material automobile roof middle cross beam and the molding method thereof as claimed in claim 4, characterized in that: The preparation process described in step S2 requires that polypropylene, a compatibilizer and a coupling agent are uniformly mixed in a high-speed mixer, and then the mixed molten resin is extruded into an impregnation mold by a screw extruder, and continuous glass fibers are introduced at the same time, so that the glass fibers and the resin are impregnated in the die head, and then the impregnated continuous glass fiber impregnated material is drawn out by a traction device, and finally rolled and cooled to obtain a continuous glass fiber reinforced polypropylene unidirectional prepreg tape.
8. The composite material automobile roof middle cross beam and the molding method thereof as claimed in claim 4, characterized in that: In step S3, it is required to lay the metal mesh after electroplating and phosphating treatment between the two layers of composite material prepreg, and then put the above-mentioned laminated composite material into a double steel belt press for continuous roller forming to obtain a composite material laminate; the upper and lower rollers of the press apply pressure to the composite material in the middle; the spacing between the upper and lower layers of steel belts is controlled to be 2.1 mm.
9. The composite material automobile roof middle cross beam and the molding method thereof as claimed in claim 4, characterized in that: In step S4, the four bolt holes on the left and right are used to fix the laminate on the lower mold using positioning pins; during molding, a release agent is first applied to the upper and lower mold surfaces of the mold, and preheating is started. After completion, the molten composite laminate is sent to the mold station, the mold is closed, and the temperature and pressure are increased, the temperature and pressure are maintained, and the temperature and pressure are reduced. After that, the mold is opened and the top cover middle beam blank is taken out for post-processing such as trimming and deburring, and the top cover middle beam part can be obtained.
10. A composite material automobile roof middle cross beam, characterized in that: The molding method is adopted according to any one of claims 1 to 9.
Citation Information
Patent Citations
Carbon fiber composite material automobile roof middle cross beam
CN111038596A
A continuous glass fiber reinforced nylon composite roof beam and vehicle
CN113147905B